2012
DOI: 10.1002/pola.26392
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid‐ and carbonate‐based crosslinked polymeric micelles for drug delivery

Abstract: Our objective was to synthesize and evaluate lactic acid-and carbonate-based biodegradable core-and core-corona crosslinkable copolymers for anticancer drug delivery. Methoxy poly(ethylene glycol)-b-poly(carbonate-co-lactide-co-5-methyl-5-allyloxycarbonyl-1,3-dioxane-2-one) [mPEG-b-P(CBco-LA-co-MAC)] and methoxy poly(ethylene glycol)-b-poly(acryloyl carbonate)-b-poly(carbonate-co-lactide) [mPEG-b-PMAC-b-P(CB-co-LA)] copolymers were synthesized by ring-opening polymerization of LA, CB, and MAC using mPEG as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 41 publications
(57 reference statements)
0
29
0
Order By: Relevance
“…Polyethylene glycol (PEG) is one of the best choice as hydrophilic segment for its several interesting features, including prolonged circulation time, enhanced permeability and retention effect (EPR effect) improved drug tolerance and so on [8,9]. Biodegradable aliphatic polycarbonates have been used as the hydrophobic core of copolymer micelles due to their low toxicity, favorable mechanical properties and biodegradability [10], while the properties of aliphatic polycarbonates could be further controlled for different applications by introducing pendant functional groups [11]. In our previous studies, immobilized porcine pancreas lipase on silica particles (IPPL) has proven to be a powerful catalyst for the ROP of cyclic carbonates such as 5-allyloxy-1,3-dioxan-2-one (ATMC), dimethyltrimethylene carbonate (DTC) and other kinds of cyclic monomers [12][13][14], while amphiphilic block copolymers based on aliphatic polycarbonates could also be prepared by enzymatic methods using PEG as a macroinitiator [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene glycol (PEG) is one of the best choice as hydrophilic segment for its several interesting features, including prolonged circulation time, enhanced permeability and retention effect (EPR effect) improved drug tolerance and so on [8,9]. Biodegradable aliphatic polycarbonates have been used as the hydrophobic core of copolymer micelles due to their low toxicity, favorable mechanical properties and biodegradability [10], while the properties of aliphatic polycarbonates could be further controlled for different applications by introducing pendant functional groups [11]. In our previous studies, immobilized porcine pancreas lipase on silica particles (IPPL) has proven to be a powerful catalyst for the ROP of cyclic carbonates such as 5-allyloxy-1,3-dioxan-2-one (ATMC), dimethyltrimethylene carbonate (DTC) and other kinds of cyclic monomers [12][13][14], while amphiphilic block copolymers based on aliphatic polycarbonates could also be prepared by enzymatic methods using PEG as a macroinitiator [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The strong H‐bonding functionalities of PEG‐ b ‐poly(ethyl‐random‐urea carbonate) BCPs not only reduced critical micelles concentration of the BCP (to 1/4 ×) in aqueous environment compared to conventional PEG‐ b ‐PTMC BCP without the noncovalent stabilization, but also improved kinetic stability of micelles and doxorubicin (DOX)‐loaded micelles in the presence of a destabilizing agent . Furthermore, Danquah et al synthesized and evaluated lactic acid‐ and carbonate‐based biodegradable core‐ and core‐corona crosslinkable copolymers for anticancer drug delivery. Crosslinked micelles demonstrated enhanced stability against extensive dilution with aqueous solvents and in the presence of physiological simulating serum concentration .…”
Section: Applicationsmentioning
confidence: 99%
“…Furthermore, Danquah et al synthesized and evaluated lactic acid‐ and carbonate‐based biodegradable core‐ and core‐corona crosslinkable copolymers for anticancer drug delivery. Crosslinked micelles demonstrated enhanced stability against extensive dilution with aqueous solvents and in the presence of physiological simulating serum concentration . Additionally, Yan et al prepared a functionalized six‐membered cyclic carbonate monomer containing a protected thiol group, MTC, and DOX was loaded into the micelles as a model drug.…”
Section: Applicationsmentioning
confidence: 99%
“…Several groups have exploited this methodology to produce core‐crosslinked micelles through micellization of block copolymers, followed by crosslinking the allyl groups present on the pendent functionality. Polycarbonates which have been used for this purpose include PMAC, PAC, and a cinnamate‐functional carbonate, 5‐methyl‐5‐cinnamoyloxymethyl‐1,3‐dioxan‐2‐one (MC) . Research by Wu and co‐workers and separately by Danquah et al has shown that such core‐crosslinked micelles possess improved properties, such as increased thermal stability and reduced aggregation, and greater resistance to water dilation and organic solvents in comparison to noncrosslinked micelles …”
Section: Postpolymerization Modification Of Alkene‐functional Polycarmentioning
confidence: 99%